KAJIAN SELEKSI SUMBER MIKROORGANISME PEMBENTUK BIOGAS DARI AIR LIMBAH INDUSTRI SAGU - Yuliastini, Siluh Made; Hasanudin, Udin; Suroso, Erdi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
Sago industry is one of the industries that generate wastewater with high levels of pollution load. High load of the wastewater can be reduced by anaerobic digestion methods. However, phenolic compounds derived from the sago trunk cause problems on the activity of microorganisms in anaerobic digestion. The purposes of this research were to select source of microorganisms which capable to decompose organic matter and to know their capabilities on biogas production from sago industrial wastewater. Sources of microorganisms used in this study were sludge from WWTP of sago industry, and microorganism, commercially known as Activated Growth and BioCK. Sago industry wastewater were fermented in stirred bioreactor. Each bioreactor contained 20% source of microorganisms and 80% of sago industry wastewater. Each treatment was adapted for 7 days and value of pH, SCOD, Total Suspended Solid (TSS), Volatile Suspended Solid (VSS) and the gas volume was analyzed on the eight day. The result showed that the best source of microorganisms which was capable of degrading organic matter from sago industry wastewater into biogas was the sludge from WWTP of sago industry. With the Hydraulic Retention Time (HRT) of 66 days, the sludge from WWTP of sago industry was able to reach 55.79% SCOD removal, biogas production of 200 mL, pH value of 5.75, TSS 17 187 mg / L, VSS 12 296 mg / L, ratio of VSS / TSS 0.7129 mgVSS / mgTSS, Keywords : biogas, phenolic, sago, SCOD removal, sludge, wastewater